A study on clinico etiological spectrum of intestinal obstruction in paediatric age group - Memon, M. Amin; Patel, Jiwan Lal; Siddharth, Ram Kumar; Dhuware, Mahendra Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Acute intestinal obstruction is very common surgical emergencies in paediatric age. There are many surgical causes for morbidity and mortality in paediatric age group of which intestinal obstruction giving large contribution. In most of studies child survival after surgical procedures for intestinal obstruction was good while the death rates were more when there was delay in presentation, and management. Morbidity, complications and mortalities are more severe when presented late. There is a delay in the initial presentation of intestinal obstruction cases due to various reasons. Methods: Present study enrolled all the patients presenting with signs and symptoms of intestinal obstruction in Paediatric surgery unit of Dept. of surgery of Dr. BRAM Hospital, Raipur (C.G.), India during January 2014 to August 2015. Patients with intestinal obstruction were admitted in paediatric surgery ward with provisional diagnosis of acute intestinal obstruction. Immediately after admission, conservative management started till the hydration and urine output becomes normal. Routine and specific investigations were done. As the study includes most of cases of acute dynamic intestinal obstruction most of cases after initial resuscitation were managed by appropriate procedures. Postoperative care was done and outcome of the study was noted. Results: Maximum cases of intestinal obstruction were in neonatal period and least in 5-14 years. Sex ratio is 2.5:1 (male to female). ARM was the major cause of obstruction in neonatal (<1 month) age group. IHPS and Hirschsprung’s disease were most common cause of GI obstruction in 1 month to 1 year age group in our study. 4 of our cases did not have accurate diagnosis and were responded well to conservative management. Most of the patients presented with complain of not passing stool followed by distension of abdomen. 85.94% of cases are congenital in our study. Large gut portion was involved in majority of cases. Overall survival rate was 91.40%. Conclusions: Present study concludes that congenital causes are more common in paediatric intestinal obstruction cases. Early diagnosis and intervention are crucial factors to improve the outcome.